Sodium metasilicate-activated one-part geopolymer concrete: Impact strength assessment with bottom ash substitution and fiber reinforcement - Samadi M.; Wong L.S.; Murali G.; Abdul Shukor Lim N.H.; Abdulkadir I.; Tan S.Q.; Chan Y.T. (Elsevier Ltd, 2025)
This study aims to investigate the effect of fibers on the impact strength of fibrous one-part geopolymer concrete (OPGC) to mitigate its brittleness. This research examines the impact strength of OPGC activated with sodium metasilicate pentahydrate, utilizing fly ash as a precursor material. The study uniquely explores the effects of bottom ash, substituted at varying levels (25 % to 100 %) for sand, within the OGPC matrix. Additionally, incorporating two distinct fiber types, polypropylene and kenaf, individually at 0.5 % and in a hybrid combination at 0.25 % each, offers a fresh perspective on fiber reinforcement in OGPC. Scanning electron microscopy and X-ray diffraction provide critical insights into the microstructural and mineralogical properties of the developed OPGC. The impact strength of OPGC with this specific combination of materials has not been previously investigated by any researchers, establishing the novelty of this study. Results revealed that the combination of fibers with 25 % BA exhibited a synergistic effect, leading to a notable enhancement in impact strength. Conversely, the impact strength declined with other combinations of materials. Polypropylene fibers demonstrated the highest performance in terms of impact strength for OPGC, followed by the hybrid fiber combination, with kenaf fibers exhibiting the lowest performance in this regard. ? 2024 The Authors